Autohemoterapia Menor Ozonizada Como Alternativa Terapéutica Para El Tratamiento De Dermatitis Atópica En Caninos (Reportes De Caso) (2022)
The research project is carried out as an alternative for therapeutic management of canine atopic dermatitis (CAD), taking into account that the treatments used Currently they are based on the control of the signology generated secondary to the presentation of this disease.